Dendronephthya sp. is a soft coral that has huge distribution starting from Indopacific, Tonga, Solomon Islands to Great Barrier Reef in Australia. However, this soft corals survive only in short period after cultivation in artificial habitat (aquarium). Recent study showed that the soft coral Dendronephtya sp. has an association or symbiotic relationship with several bacteria, commonly known as coral associated bacteria (CAB). In this study, we compared the population dynamic of Dendronephthya - SUSAN SOKA; RORY ANTHONY HUTAGALUNG; . YOGIARA; CLARA ASSISI (HAYATI Journal of Biosciences, 2011)
Dendronephthya sp. is a soft coral that has huge distribution starting from Indopacific, Tonga, Solomon Islands to Great Barrier Reef in Australia. However, this soft corals survive only in short period after cultivation in artificial habitat (aquarium). Recent study showed that the soft coral Dendronephtya sp. has an association or symbiotic relationship with several bacteria, commonly known as coral associated bacteria (CAB). In this study, we compared the population dynamic of Dendronephthya sp.-associated bacteria in natural and artificial habitat, resulting different bacterial community profiles using terminal restriction fragment length polymorphism (T-RFLP) analysis of bacterial community DNA. There were 15 main classes of bacterial population identified along with uncultured microorganism, uncultured organism, uncultured bacteria and unidentified organism. Members of Actinobacteria, Arthrobacteria, Chlorobia, Caldilineae, d-proteobacteria and Proteobacteria were predicted to give contributions in the survival ability of both Dendronephthya sp. The cultivation of soft corals after 2 weeks in artificial habitat increases bacterial population similarity on 2 different samples by 10%. Bacterial population similarity in artificial habitat would increase along with the longer cultivation time of soft corals.